2002
DOI: 10.1097/00007890-200205150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of donor-specific tolerance by adenovirus-mediated cd40ig gene therapy in rat liver transplantation1

Abstract: Blockade of CD40-CD154 pathway by CD40Ig gene therapy is a potent alloantigen-specific immunosuppressive strategy to induce permanent acceptance of liver allograft and would be a new therapeutic candidate in a clinical liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Among several co-stimulatory signals, the CD40-CD154 pathway is a representative cascade that has been shown to play a central role in the activation of immune cells, including T cells, and in the priming of alloimmune responses (44,45). Blockade of this signaling pathway by various approaches has been shown to induce potent immunosuppression against cellular immunity and tolerance to allografts in experimental organ transplantation (46)(47)(48). In PITx, Adams et al (17) demonstrated that Chi220, which is a chimeric IgG1 CD40-specific mAb, dramatically prolonged islet allograft survival to 237, 237, 220, >185 and 172 days when combined with LEA29Y (belatacept).…”
Section: Discussionmentioning
confidence: 99%
“…Among several co-stimulatory signals, the CD40-CD154 pathway is a representative cascade that has been shown to play a central role in the activation of immune cells, including T cells, and in the priming of alloimmune responses (44,45). Blockade of this signaling pathway by various approaches has been shown to induce potent immunosuppression against cellular immunity and tolerance to allografts in experimental organ transplantation (46)(47)(48). In PITx, Adams et al (17) demonstrated that Chi220, which is a chimeric IgG1 CD40-specific mAb, dramatically prolonged islet allograft survival to 237, 237, 220, >185 and 172 days when combined with LEA29Y (belatacept).…”
Section: Discussionmentioning
confidence: 99%
“…Some differences in these models, such as different molecules (CD40Ig versus anti-CD40L), the continuous presence of CD40Ig versus only inductive treatment with anti-CD40L, and the species used may explain this discrepancy. CD40Ig also induced indefinite survival of allogeneic livers (31), but the role of CD4 + or CD8 + Tregs was not analyzed. Anti-CD40L mAbs have been proposed to act at least in part through depletion of activated CD4 + T cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral-mediated transfer of the gene encoding CD40-Ig into rat livers resulted in long-term survival following transplantation into allogeneic recipients. 9 Immunocompetence was tested by analyzing skin allograft survival 120 days after liver transplantation, long after CD40-Ig production had ceased. Therefore, it is unclear whether recipients were able to respond to third-party antigens at earlier time points while CD40-Ig was expressed in the transplanted livers.…”
Section: Prospectsmentioning
confidence: 99%